Influence of Al-B grain refiner on porosity formation of directionally solidified Al-Si alloys - Uludağ, Muhammet (Springer Singapore Pte Ltd, 2020)
This work aims to present a perspective for porosity formation in three different alloys: A356, A413 and A380.1 by taking into account the addition of Al-B grain refiners: AlTi(5)B(1)and Al3B. The directional solidification method was used, and microstructural changes of the alloys and its correlation with porosity formation were investigated. Pore size, number of pores, average pore length and distribution of pores were statistically analyzed. Also, external shrinkage was examined, and the volume of external shrinkage was calculated. It was found that there was a relationship between external shrinkage and the size and number of pores. As the size and number of pores internally decrease, external shrinkage increases. Additionally, porosity is decreased in all the three Al-Si alloys when Al-B grain refiners are used. The distribution of pore diameters is low when AlTi(5)B(1)is used. Grain refiners have a different effect on porosity formation of Al-Si alloys with regard to their solidification morphology.
Keywords: Al-Si alloys; directional solidification; grain refinement; internal porosity; external shrinkage; TG146; 21; A